Who Am I? : Baby animals - Gardner, Charlie; Harvey, Victoria (New York, NY : Dorling Kindersley Limited, 2014)
Simple facts and photographs ask young readers to guess which farm animals are hiding behind peepholes
Age 15 months
Text in English
Keywords: Domestic animals -- Juvenile literature; Board books